Classification and selection of tenants in residential real estate: a constructivist approach - Fonseca, M. B. C. B. F. (2018)
Choosing a tenant is a key issue in the housing rental market. Knowing, a priori, whether a tenant will pay the rent on time, be able to hold a good relationship with the neighbors or take care of the property (i.e. whether s/he will be a “good” tenant) is not a simple endeavor. It is crucial, however, as it can help save time, money and conflicts that can end up in court. This study aims to address this issue, through the integrated use of cognitive maps and the Decision EXpert (DEX) technique. Grounded on a constructivist logic, the study brought together a panel of experts with experience and knowledge in the residential rental market, in order to identify and articulate the criteria to be taken into account in the classification and selection of tenants. The results achieved show that the integration of these two methodologies (i.e. cognitive maps and DEX) can help increase our understanding of the decision problem at hand, and lead to more informed and potentially better tenant choices. Advantages and limitations of the framework are also discussed.